2009
DOI: 10.3917/riges.343.0128
|View full text |Cite
|
Sign up to set email alerts
|

L'empiétement du travail des femmes et des hommes cadres sur leur vie personnelle

Abstract: Distribution électronique Cairn.info pour HEC Montréal. © HEC Montréal. Tous droits réservés pour tous pays.La reproduction ou représentation de cet article, notamment par photocopie, n'est autorisée que dans les limites des conditions générales d'utilisation du site ou, le cas échéant, des conditions générales de la licence souscrite par votre établissement. Toute autre reproduction ou représentation, en tout ou partie, sous quelque forme et de quelque manière que ce soit, est interdite sauf accord préalable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
(8 reference statements)
0
2
0
3
Order By: Relevance
“…Several empirical studies reveal that the growth of technology and its uses increase the fragmenting of work tasks and the workday, blur the boundary between work and personal life, and encourage the invasion of professional life into personal life (Genin, 2009; Tabassum and Rahman, 2013; de Wet and Koekemoer, 2016; Kossek, 2016). Indeed, the use of ICTs for work fosters the encroachment of work on life outside of work, and makes the border between personal life and work life more porous, as employees find it very difficult to establish a limit between these two areas of existence (Isaac et al, 2007; Park and Jex, 2011; Thomas, 2014; de Wet and Koekemoer, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several empirical studies reveal that the growth of technology and its uses increase the fragmenting of work tasks and the workday, blur the boundary between work and personal life, and encourage the invasion of professional life into personal life (Genin, 2009; Tabassum and Rahman, 2013; de Wet and Koekemoer, 2016; Kossek, 2016). Indeed, the use of ICTs for work fosters the encroachment of work on life outside of work, and makes the border between personal life and work life more porous, as employees find it very difficult to establish a limit between these two areas of existence (Isaac et al, 2007; Park and Jex, 2011; Thomas, 2014; de Wet and Koekemoer, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…With regard to the use of ICT outside traditional workplaces and hours, studies show that the intrusion of work into personal life is often the cause of conflicts with partners, family members, and more broadly significant others (Kossek and Lautsch, 2008; Leonardi et al, 2010; Ayyagari et al, 2011). Many researchers found that employees increasingly respond, or are encouraged to respond, to e-mails, text messages, or professional phone calls during their free time, which leads to work overload, role ambiguity, and work–life conflict, ultimately promoting the perception of stress, technostress, techno-invasion, and burnout (Isaac et al, 2007; Kossek and Lautsch, 2008; Genin, 2009; Leonardi et al, 2010; Ayyagari et al, 2011; Park and Jex, 2011; Tabassum and Rahman, 2013; Thomas, 2014; Ferguson et al, 2016; Leung and Zhang, 2017). Previous studies generally point out that the use of ICTs for professional purposes outside usual working hours favors disruption of family activities and the perception of work–family conflict, from the point of view of employees as well as their significant others (Boswell and Olson-Buchanan, 2007; Fenner and Renn, 2010; Matusik and Mickel, 2011; Wright et al, 2014; Carlson et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Des études françaises révèlent qu'un travailleur sur quatre amènerait souvent ou parfois du travail à la maison et que cette proportion atteindrait 75% chez les cadres (Bergère et Chassard, 2013;Bozon et al, 2010). Si le travail à la maison et plus généralement la porosité des temps ne sont pas des nouveautés, les technologies mobiles confèrent une ampleur nouvelle à ces phénomènes (Fenner et Renn, 2010;Hislop et Axtell, 2011;Matusik et Mickel, 2011;Genin, 2009;Duxbury et Smart, 2011;Perlow, 2012). Pour gérer les frontières entre les différents temps de la vie, les individus auraient recours à différentes stratégies se situant sur un continuum allant de la segmentation à l'intégration (Clark, 2000).…”
Section: Conciliation Vie Personnelle -Vie Professionnelleunclassified
“…Le travail à la maison représente une solution utile pour limiter le temps de transport, le temps passé au bureau, les interruptions dans le travail ou concilier des obligations professionnelles et familiales (Felstead et al, 2002;Van Dyne et al, 2007;Tremblay & Genin, 2010). Cependant, de nombreuses études montrent que les personnes qui travaillent à la maison le font d'abord pour terminer des tâches qu'elles n'ont pas eu le temps de réaliser dans les horaires normaux de bureau, traduisant une intensification du travail (Halford, 2005;Middleton et Cukier, 2006;Genin, 2009;Metzger, 2009;Fenner et Renn, 2010;Matusik et Mickel, 2011). L'incidence des technologies mobiles et du travail à la maison sur la conciliation vie personnelle -vie professionnelle apparait donc ambigüe et multiforme : représentent-ils une forme de mise à disposition en continu pour le travail ou un mode de conciliation efficace ?…”
Section: Conciliation Vie Personnelle -Vie Professionnelleunclassified
See 1 more Smart Citation